2019
DOI: 10.1007/978-3-030-22196-6_35
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls Measuring 1D Inertial Particle Clustering

Abstract: Clustering is an important phenomenon in turbulent flows laden with inertial particles. Although this process has been studied extensively, there are still many open questions about both the fundamental physics and the reconciliation of different observations into a coherent quantitative view of this important mechanism for particle-turbulence interaction, that can enable high resolution modeling.In this work, we study the effect of projecting this phenomenon onto 2D and 1D (as usually done in experimental mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In this work, we refrained from analyzing the preferential concentration from 1D particle records, for instance via 1D Voronoï tessellations [44], as a previous work from the group suggests that these statistics in our experimental setup may present biases that could lead to misleading conclusions see [45]. Nonetheless, the presence of clusters (higher density regions with respect to the average concentration) and voids (lower density regions with respect to the average concentration) may be of relevance in this problem.…”
Section: B Velocity Measurements and Angle Correctionmentioning
confidence: 99%
“…In this work, we refrained from analyzing the preferential concentration from 1D particle records, for instance via 1D Voronoï tessellations [44], as a previous work from the group suggests that these statistics in our experimental setup may present biases that could lead to misleading conclusions see [45]. Nonetheless, the presence of clusters (higher density regions with respect to the average concentration) and voids (lower density regions with respect to the average concentration) may be of relevance in this problem.…”
Section: B Velocity Measurements and Angle Correctionmentioning
confidence: 99%
“…The key points in figure 3(b) are the very sharp increase in σ voronoi observed at the homogeneous-heterogeneous transition, and the large value, well above that of an RPP, that σ voronoi reaches at high V sg . The shortcomings of 1-D Voronoï analysis in complex flows have been discussed elsewhere (Mora et al 2018(Mora et al , 2019: one key result is that the clear difference observed with the standard deviation of an RPP unambiguously demonstrates that clustering does occur in the present flow conditions. Furthermore, for all heterogeneous conditions investigated (that is, for V sg up to 24 cm s −1 ), the standard deviation σ voronoi remains nearly the same: that feature also indicates that clustering is a central characteristic of the heterogeneous regime.…”
Section: Local Void Fraction and Identification Of Meso-scale Structuresmentioning
confidence: 99%
“…Paralleling what we did for turbulent particle-laden flows (Monchaux, Bourgoin & Cartellier 2010;Sumbekova et al 2017;Mora et al 2018), we exploit 1-D Voronoï tessellations built from the gas phase indicator function X G (t) (Raimundo 2015;Mezui, Cartellier & Obligado 2018;Raimundo et al 2019). Here, X G (t) is deduced from the signal delivered by an optical probe.…”
Section: Local Void Fraction and Identification Of Meso-scale Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Just downstream of it, a rack of spray nozzles produced polydisperse inertial water droplets [21]. This wind tunnel has been extensively used to study particle-turbulence interaction under homogeneous isotropic turbulent (HIT) conditions (more experimental details are described in [22][23][24]). The measuring station was located three meters (3m) downstream the active grid, and at the center line of the wind tunnel, where HIT and the classical scalings from K41 theory have been recovered [15].…”
mentioning
confidence: 99%